Senior High School Students’ Perceptions of Using Canva for Their Descriptive Text Presentation - Salsabila Shendy Aulia; Him’mawan Adi Nugroho (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to analyse what are Senior High School Students’ Perceptions of using Canva for Descriptive Text Presentation. Moreover, it also Examines how Canva helps Senior High School Students to support their Presentation for Structuring and Delivering Descriptive Text. The method in this study is a qualitative method. The data instruments were 20 open-ended questions in questionnaire filled by 33 students shared via Google form and 12 interview questions answered by top 10 students at State Senior High School in Gresik Jawa Timur) batch 2024/2025. The results of this study reveals that high school students perceive Canva as a highly effective tool for preparing and delivering descriptive text presentations. Additionally, students perceive Canva as a helpful tool for making and organizing presentations. It encourages creativity, confidence, and active participation while also supporting language skills, clear thinking, and audience awareness. These benefits highlight Canva’s value in both learning and presentation tasks.